Using spatial syntax and GIS to identify spatial heterogeneity in the main urban area of Harbin, China - Sun, Ming; Meng, Qingxiang (Frontiers in Earth Science, 2022)
The discourse about urban planning, urban design, urban management, and many other basic urban planning issues are related to identifying the spatial heterogeneity in the main urban area (MUA). Road networks are important infrastructure for social and economic development and it is also an important driving factor for urban land use. Therefore, the topological characteristics of the urban road network can be used as an important basis for the space of the division of MUA. This paper takes the MUA space in the Harbin Ring Expressway as the research object. The findings of this research establish a city model to identify the spatial heterogeneity, through a method of ‘Spatial essential attribute - Spatial autocorrelation analysis - Establishment of urban model’. In this model, spatial essential attributes are obtained from the analysis of space syntax. Spatial autocorrelation analysis is a method to calculate spatial clustering, and building the urban model is a kind of computer visualization method. Using this method, this research constructs a Spatial Heterogeneity Model (SHM) of the urban built-up area in Harbin, which consists of three layers of spatial circles and two prominent regional structures. Then, it analyzes the spatial distribution of infrastructure and population agglomeration through nuclear density. We gain three conclusions: Firstly, in addition to educational and greening facilities, the spatial distribution of infrastructure is correlated with the regional structure of SHM in Harbin’s MUA. Secondly, there are differences in the spatial attraction of population agglomeration between the different areas in SHM of Harbin’s MUA. Finally, the new identification model of SHM is scientific, but it has some advantages and demerits. Using spatial topological values to construct SHM, it provides a new city model in urban spatial heterogeneity region recognition. Through the research results, the identification method of SHM improves the traditional method which identifies urban heterogeneity areas according to people’s subjective wishes in urban planning. Therefore, SHM helps relevant practitioners and scholars practice urban planning, urban analysis, urban protection, and urban management.